Student The Importance of Using Computer Technologies in Mental Education of Young People (Progress Annals: Journal of Progressive Research, 2024)
This article is devoted to the issues of the content of the use of computer technologies in the mental education of students. It is also desirable to use the achievements of computerization of educational processes. The importance of effective use of modern computers in the educational process has been studied.